Generating alternative worlds - Čerče, Danica (ELOPE (Ljubljana), 2010)
Since the 1980s, indigenous authors have had a high profile in Australia and their writing has made a significant impact on the Australian public. Given that poetry has attracted more indigenous Australians than any other mode of creative expression, this genre, too, has provided an important impetus for their cultural and political expression. Discussing the verse of Romaine Moreton, and taking up George Levine's view (2000) that works of art are able to produce critical disruptions and generate alternative worlds, the article aims to show that Moreton's mesmerising reflections on origin, dispossession, dislocation and identity of Australian indigenous peoples encouraged national self-reflection and helped create a meaningful existence for the deprived and the dispossessed. It also touches upon some other topics explored in Moreton'spoetry and provides evidence of its universal relevance.
Keywords: angažirana poezija; Australian literature; Australian poetry; avstralska književnost; avstralska poezija; indigenous literature; inter-cultural communication; literarne študije; medkulturna komunikacija; protest poetry; staroselska književnost